Circumcision and HIV Prevention in Southern Africa: WHO Recommendations Questioned; - (:unkn) unknown (My University, 2023)
The relationship between human immunodeficiency virus (HIV) infection and male circumcision, medical or traditional, remains controversial. Randomized clinical trials indicate that medical circumcision reduces the incidence in the months following surgery. But population-based studies show that the prevalence is the same over the long term. This paper summarizes the results of large population-based surveys conducted in southern African countries, the region most affected by AIDS worldwide. These surveys show that HIV prevalence among men aged 40-59 years is the same regardless of circumcision status and type. These results call into question the recommendations of the World Health Organization. Copyright
Keywords: African Research